2001
DOI: 10.1111/j.1447-0756.2001.tb01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis in Early Pregnancy and Adverse Pregnancy Outcome

Abstract: Presence of BV in early pregnancy is associated with an increased risk of PTB and PROM. Multicentric interventional study is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…The observed PTB rate of 7% in this study is similar to the expected rate in Flanders during the same period (7.4%; singletons 6.3%) 11 . Numerous studies have consistently shown that bacterial vaginosis and AVF at 12–24 weeks are associated with increased risks of PTB, preterm rupture of the membranes, chorioamnionitis, fetal infection and cerebral palsy 12–22 . However, studies applying strict criteria for full bacterial vaginosis (a Nugent score above 7, overall granular flora, >20% clue cells and LBG III) did not find a significant correlation between BV and the risk of PTB 14,18,23 …”
Section: Discussionmentioning
confidence: 99%
“…The observed PTB rate of 7% in this study is similar to the expected rate in Flanders during the same period (7.4%; singletons 6.3%) 11 . Numerous studies have consistently shown that bacterial vaginosis and AVF at 12–24 weeks are associated with increased risks of PTB, preterm rupture of the membranes, chorioamnionitis, fetal infection and cerebral palsy 12–22 . However, studies applying strict criteria for full bacterial vaginosis (a Nugent score above 7, overall granular flora, >20% clue cells and LBG III) did not find a significant correlation between BV and the risk of PTB 14,18,23 …”
Section: Discussionmentioning
confidence: 99%
“…Patient with BV have a sixfold increased rate of postpartum endometritis after cesarean section, a threefold increased rate of pelvic inflammatory disease after therapeutic abortion, and a three–fourfold increased rate of vaginal cuff cellulitis after abdominal hysterectomy. Pregnant patients with BV have a 50–100% increased rate of preterm low birthweight delivery, amniotic fluid infection and chorioamnionitis 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…Pregnant patients with BV have a 50-100% increased rate of preterm low birthweight delivery, amniotic fluid infection and chorioamnionitis. [8][9][10] Various studies have shown an association between urinary tract infection and abnormal vaginal infection. Harmanli et al studied women who presented for routine gynecologic examination and found that 22.4% with urinary tract infection also had BV compared with 9.7% without BV.…”
Section: Introductionmentioning
confidence: 99%
“…The vast amount of interest in these areas is because of the adverse effects disturbances of the urogenital flora present, especially during pregnancy (including premature births, low birth weight children and other complications). 37,38,39 The urogenital tract can be divided into two distinct regions: the urinary tract and the vagina. In health, the urinary tract is generally considered to harbour minimal levels of bacteria.…”
Section: The Microflora Of the Female Urogenital Tractmentioning
confidence: 99%